Proteomic Analysis of Serum Lysine Acetylation in Uyghur Patients With T2DM - Wang, Xuemei; Cai, Weijuan; Yin, Liang (Frontiers in Molecular Biosciences, 2022)
Lysine acetylation is a reversible modification process after protein translation, which plays a key regulatory role in various metabolic diseases such as diabetes. The prevalence of type 2 diabetes mellitus (T2DM) in Uyghur population is higher, but the acetylation status of proteomics in Uyghur with T2DM is still unclear. Herein, we performed a proteomic quantitative study of lysine acetylation in T2DM patients using Tandem Mass Tags (TMT) labeling, acetylation enrichment techniques and high-resolution liquid chromatography-tandem mass spectrometry. We quantify 422 acetylation sites on 120 proteins, of which 347 sites of 103 proteins contained quantitative information. Compared with the control, we found that a total of 8 acetylated sites within proteins were significantly differentially expressed with 3 up-regulated and 5 down-regulated. including histones H4 and H3.3C. Meanwhile, we completed bioinformatics analysis, including protein annotation, functional classification, functional enrichment and cluster analysis based on functional enrichment. In addition, the mRNA (ApoB-100, histone H4 and H3.3C) and protein (histone H4 and H3.3C) levels were verified through 60 samples. Besides, we also performed histone H4 chromatin immunoprecipitation analysis at the level of INS-1 cells. These could be potentially useful markers for prediction of prediabetes and also provides a basis for the pathogenesis of T2DM.